Pengaruh Kepemimpinan Transformasional, Lingkungan Kerja, Kepuasan Kerja Dan Komitmen Pegawai Terhadap Kinerja Pegawai Pada Sub Bagian Tata Usaha Pimpinan Staf Ahli Dan Kepegawaian – Bagian Umum Sekretariat Daerah Kabupaten - Elnike Priskila Mau (Peneliti.net, 2023)
Performance is a result of work produced by an employee in achieving the expected goals. In addition, the performance of an employee is an individual thing, because each employee has a different level of ability - different in carrying out their duties. Performance itself means the result of work or work performance. An employee is said to be successful if the results of the work reach even more than the standards set. Performance problems are inseparable from work performance, but it needs to be understood that performance is not just the result of work or work performance, but also includes how the work process takes place in order to achieve the goals of the organization. This study aims to determine the effect of transformational leadership on the work environment, job satisfaction and employee commitment. The population and sample in this study were employees in the Administrative Sub-Division of Expert Staff and Personnel Management - General Section of the Regional Secretariat of Alor Regency, totaling 30 people. The sampling technique in this study is a saturated sample. The statistical method used in this research is multiple linear regression. This type of research is quantitative research with data collection techniques, namely observation, interviews and documentation studies. The results of this study indicate that: (1) Partially the Transformational Leadership variable has a significant value of 0.000 or 0% where this value is smaller than the alpha value of 0.05 or 5% so that the results of this study accept H1 which states that Transformational Leadership is partially has a positive effect on employee performance in the Administrative Subdivision of Expert Staff and Personnel Management - General Section of the Regional Secretariat of Alor Regency. (2) Partially the work environment variable has a significant value of 0.026 or 1% where this value is smaller than the alpha value of 0.05 or 5% so that the results of this study accept H2 which states that the work environment partially has a positive effect on employee performance in the Administrative Sub-Division of Expert Staff and Personnel Leadership - General Section of the Regional Secretariat of Alor Regency. (3) Partially the variable Job Satisfaction has a significant value of 0.021 or 1% where this value is smaller than the alpha value of 0.05 or 5% so that the results of this study accept H3 which states that Job Satisfaction partially has a positive effect on employee performance in Sub Administrative Section of Expert Staff and Personnel Leadership - General Section of the Regional Secretariat of Alor Regency. (4) Partially the variable Employee Commitment has a significant value of 0.002 or 1% where this value is smaller than the alpha value of 0.05 or 5% so that the results of this study accept H4 which states that Employee Commitment partially has a positive effect on Employee Performance in Sub Administrative Section of Expert Staff and Personnel Leadership - General Section of the Regional Secretariat of Alor Regency. (5) Partially the variable Transformational Leadership Work Environment Job Satisfaction and Employee Commitment has a significant value of 0.000 or 0% where this value is smaller than the alpha value of 0.05 or 5% so that the results of this study accept H5 which states that Transformational Leadership in the Work Environment Job Satisfaction and Employee Commitment partially have a positive effect on employee performance in the Administrative Subdivision of Expert Staff and Personnel Leadership - General Section of the Regional Secretariat of Alor Regency. (6) The magnitude of the influence of the variable Transformational Leadership Work Environment Job Satisfaction and Employee Commitment is 91.0% this study simultaneously received H5.